A new method to determine stretch reflex latency. Issue 6 (15th October 2021) - Topkara, Betilay; Aydin, Tugba; Corum, Mustafa; Karaoglu, Ayse; Ekici Zincirci, Dilara; S Bugdayci, Derya; Ones, Kadriye; Paker, Nurdan; Kesiktas, Nur; Karacan, Ilhan; Türker, Kemal S.
Abstract: Introduction/Aims: Motion artifact signals (MASs) created by the relative movement of intramuscular wire electrodes are an indicator of the mechanical stimulus arrival time to the muscle belly. This study proposes a method that uses wire electrodes as an intramuscular mechanosensor to determine the stretch reflex (SR) latency without lag time. Methods: Gastrocnemius SR was induced by tendon tap, heel tap, and forefoot tap. The MASs recorded by intramuscular wire electrodes were extracted from background electromyographic activity using the spike‐triggered averaging technique. Simultaneous recordings were obtained from multiple sites to validate the MAS technique. Results: Using intramuscular wire electrodes, the MASs were successfully determined and extracted for all stimulus sites. In the records from the rectus femoris, MASs were also successfully extracted; thus, the reflex latency could be calculated. Discussion: Wire electrodes can be used as an intramuscular mechanosensor to determine the mechanical stimulus arrival time to the muscle belly.